In Vivo Imaging of the Inner Ear at 7T MRI: Image Evaluation and Comparison With 3T. Issue 4 (April 2015) - van Egmond, Sylvia L.; Visser, Fredy; Pameijer, Frank A.; Grolman, Wilko
Abstract : Objective: The implementation of 7T magnetic resonance imaging for human use has the potential to further advance spatial resolution beyond that of 3T. This could result in potential advantages in the depiction of the membranous structures of the inner ear. The inner ear is particularly challenging to visualize at 7T because of its anatomic location, which can lead to susceptibility banding artifacts and signal loss. Study Design: Three healthy volunteers underwent magnetic resonance imaging at 3T and 7T scanner. At 7T, a unilateral dielectric pad was used for image optimization. Scan duration therefore doubled to a total of 15 minutes at 7T. Methods: The depiction of 10 anatomic parts of the inner ear was evaluated by two independent readers using a four-point grading scale. Results: The interscalar septum, utricular macula, and the nerve bundles in the internal auditory canal were visualized more clearly at 7T. Conclusion: Although reduction of image artifacts remains challenging, especially at 7T, all structures depicted at 3T could be depicted at 7T. Image quality for some anatomic structures was superior at 7T. Further improvement of image quality could be achieved by developing dedicated surface coils and by technical advancement in B1 shimming and dedicated radiofrequency pulses.